A new species of Agaporomorphus Zimmermann from Venezuela, and a review of the A. knischi species group (Coleoptera: Dytiscidae: Copelatinae) - Miller, Kelly B.; Wheeler, Quentin D. (Zootaxa, 2008)
A new species, Agaporomorphus colberti Miller and Wheeler, sp. n., is described from specimens from Departamento Amazonas, Venezuela. The new species belongs to the A. knischi Zimmermann species group based on the common presence of a pair of series of fine setae on the dorsal surface of the male median lobe of the aedeagus. Within this group, A. colberti sp. n. is sister to A. knischi and is united with that species based on broadly expanded antennomeres V and VI in the male and other general shape features of the male genitalia. An updated phylogenetic analysis of the genus is provided and the A. knischi species group is briefly reviewed with male genitalia and other relevant features illustrated.